Design and Endpoints for Clinical Trials in Primary Sclerosing Cholangitis. Issue 3 (31st August 2018) - Ponsioen, Cyriel Y.; Lindor, Keith D.; Mehta, Ruby; Dimick‐Santos, Lara
Abstract : Primary sclerosing cholangitis (PSC) is a rare and chronic liver disease for which there is no effective therapy. Interest has grown in developing treatments for this condition, with several agents proposed as potential therapies. However, there is a lack of clarity about how to measure clinical benefit in trials involving patients with this complex and rare disease. This article reviews regulatory information, the available literature on natural history, as well as potential candidate clinical and surrogate endpoints for PSC. (Hepatology 2018; 00:000‐000).